TRANSITIONAL JUSTICE PATHS: CORPORATE ACCOUNTABILITY FOR TERROR IN THE SOUTHERN CONE FACTORIES - Barros, Yamê de Oliveira; Bonfigli, Fiammetta (Revista de Direito Brasileira, 2025)
What paths have been taken and how have they developed to achieve accountability of the business sector for violations of workers' human rights on the premises of their plants? The penal persecution in Argentina of some of Ford’s directors and the first agreement by monetary indemnity between Volkswagen and Public Ministry in Brazil are a landmark for Transitional Justice with contemporary outcomes and whose regional repercussion will be of paramount importance for the construction of reparatory strategies, at the same time preserving stability in the fledgling democracies of the Southern Cone. The cross-analysis method of both recent cases makes it possible to understand the variants that influenced their respective courses, as well as tracing the media dissemination, through official and alternative means, allows measuring the social impact of the kind of measures chosen in shaping public opinion in each country. We hope to achieve an overview of the Transitional Justice paths within the framework of corporate accountability from an analysis of the efficiency and scope of the measures adopted, contributing to the improvement of reparation techniques.